Pengaruh Promosi Above The Line, Promosi Below The Line dan Experiential Marketing terhadap Minat Beli Konsumen - Sugiono, Tri; Sume, Syahlan A (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
To encourage consumers to buy, a company is required to have good advantages in the field of promotion and defense strategies so that consumers will still have buying interest in purchasing and using the product provided. Promotion methods of Above the Line, Below the Line and Experiential Marketing can be factors to built consumers’ interest in buying the product. The purpose of this study were (1) to find out how the promotion above the line of the buying interest for cellular provider, (2) to find out how the promotion of below the line on the interest to buy a cellular provider Tri, (3) to asses how experiential marketing is influencing on Tri cellular provider buying interest and (4) to find out how the promotion above the line, below the line promotions and experiential marketing influence on Tri cellular provider buying interest. The numbers of respondents in this research were 100 respondents, drawn from the students of STIE Kesatuan Bogor. The research data was processed using SPSS, 2016. The results of this study are as follows: (1) Above the Line promotion has a positive and significant effect on the quality of consumer purchase interest in a cellular provider Tri with significant value of 0,000, (2) Below the Line promotion has a positive influence and yet no significant effect on buying interest consumers on a cellular provider Tri with significant value of 0.520, (3) Experimental Marketing has a positive and significant effect on consumer purchase interest in a cellular provider Tri with significant value of 0.000 , (4) the regression equation Y = - 0,135 + 0,311X1 + 0,042X2 + 0,255X3 + ERROR. This means that the independent variable on the Below the Line promotion has a positive but insignificant effect on the dependent variable on consumer interests to purchase. The value obtained with the highest index value of 3.75 and the lowest index value obtained with a value of 3.06.